Catalyst for acrylic acid synthesis and preparation method thereof
By preparing a composite oxide catalyst containing vanadium, molybdenum, tungsten, copper, indium, and tin, and combining it with silicon carbide foam and nano-silicon carbide powder, the problems of slow catalyst reaction heat removal rate and high hot spot temperature were solved, thus achieving efficient acrylic acid production.
Patent Information
- Application Number
- CN202511440133.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-10
AI Technical Summary
Existing catalysts for the oxidation of acrolein to acrylic acid suffer from problems such as slow heat removal and high hot spot temperatures, resulting in poor catalyst stability and affecting the yield and production stability of acrylic acid.
A composite oxide catalyst containing vanadium, molybdenum, tungsten, copper, indium, and tin was used. The active component powder of the catalyst was prepared by spray drying and calcination. Silicon carbide foam was used as a carrier to combine nano-silicon carbide powder and liquid ceramic precursor to form a catalyst with high thermal conductivity. A pore-forming agent was added to form micropores, which improved the thermal conductivity and stability of the catalyst.
The conversion rate of acrolein was 98.1-99.7%, the yield of acrylic acid was 97.9-99.3%, and the hot spot temperature was controlled at 225-235℃, which significantly improved the stability of the catalyst and the ability to rapidly remove the heat of reaction.
Smart Images

Figure CN120920038A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a catalyst for the synthesis of acrylic acid and its preparation method, belonging to the field of catalyst technology. Background Technology
[0002] Acrylic acid is an important organic chemical raw material with excellent polymerization properties. It can be polymerized after esterification with methanol, ethanol, and butanol, or copolymerized with other ethylene monomers. Acrylic acid and its ester polymers are widely used in superabsorbent resins, detergents, adhesives, building materials, fibers, and plastics processing. Early acrylic acid production processes included the chloroethanol process, the Reppe process, and the acrylonitrile hydrolysis process, but these were gradually replaced due to high pollution and poor economic efficiency. Current research on acrylic acid preparation processes mainly focuses on the propane oxidation process and the propylene oxidation process. The propylene oxidation process has a higher propylene conversion rate and acrylic acid yield, and is currently the main method used in industrial acrylic acid production.
[0003] The oxidation of propylene to acrylic acid can be divided into one-step and two-step oxidation methods. In the one-step oxidation process, propylene reacts directly with air in the presence of a catalyst to produce acrylic acid. While catalysts for the one-step oxidation of propylene to acrylic acid can reduce equipment investment, the yield of acrylic acid is relatively low. Current research can only improve the yield to a certain extent and is not suitable for industrial application. The two-step oxidation process first converts propylene to acrolein, and then reacts it with air to produce acrylic acid. Currently, both domestic and international acrylic acid production plants use the two-step oxidation method. This method employs a two-reactor series operation. Propylene reacts with air in the first reactor at (300~350℃) to produce acrolein. Acrolein then reacts with supplemental air in the second reactor at (200~300)℃ to produce acrylic acid. The catalysts used are catalysts for the oxidation of propylene to acrolein and catalysts for the oxidation of acrolein to acrylic acid, respectively. Thanks to the rapid development of the two catalysts mentioned above, the synthesis of acrylic acid via the oxidation of acrolein has been widely used in industry. Catalysts for the oxidation of acrolein to acrylic acid are generally Mo-V series oxides, whose basic elements are Mo and V, with the addition of other elements to improve catalyst performance, such as Nb, Sn, Cr, W, Fe, Co, Ni, and Sb. While the application of Mo-V series oxides as catalysts for the oxidation of acrolein to acrylic acid has been widely promoted, the Mo-V active sites in these catalysts are amorphous. This amorphous structure gradually deteriorates in the high-temperature, humid environment of the acrolein oxidation process. This deterioration is mainly manifested in the loss of the active component Mo and changes in the catalyst's crystalline state. The damaged catalyst easily accumulates heat in the catalyst bed, generating hot spots. These hot spots cause localized overheating, which in turn reduces the acrylic acid yield and further exacerbates catalyst damage, creating a vicious cycle that leads to rapid catalyst deactivation and poses a significant obstacle to stable production.
[0004] Recently, those skilled in the art have improved catalyst performance and extended its service life by modifying catalyst molding methods. For example, cylindrical or hollow cylindrical catalysts currently offer advantages such as higher catalyst strength and wear resistance, a greater amount of active components, and extended service life. However, in actual acrylic acid production, hot spots frequently appear in the catalyst bed, leading to reduced catalyst activity and requiring frequent catalyst regeneration, thus shortening the production cycle of the acrylic acid plant. Spherical catalysts offer advantages such as higher effective utilization factors of active components and effective removal of reaction heat, but they are greatly affected by the molding process, resulting in significant loss of specific surface area and a decrease in catalyst activity and selectivity.
[0005] Chinese patent CN102039143A discloses a method for preparing a catalyst for the oxidation of acrolein to acrylic acid. The method involves dispersing water-soluble metal salts containing Mo, V, W, Cu, and Sb in a water / organic phase mixture at 30-100°C; maintaining an organic solvent to water weight ratio of 5-50%; reacting to generate a composite oxide precursor slurry; separating water through distillation at 20-120°C with continuous replenishment of the organic phase, ensuring the water content in the distillate is no more than 10%; then granulating by spray drying and calcining at 200-600°C to obtain the catalyst active component; mixing the initially calcined powder with molding additives and strength improvers, and using a binder to coat the active component onto the surface of an inert support, with the loading amount accounting for 5-70% of the total catalyst weight; drying the shaped product at room temperature for 5-48 hours and then calcining at 200-600°C for 1-15 hours to obtain a spherical catalyst with the active component supported on an inert support. Although the acrolein conversion rate of the catalyst obtained by this patent can reach 98.8%, the hot spot temperature is above 270℃, which is more than 20℃ higher than the reaction temperature. The rapid discharge of a large amount of reaction heat is not ideal, so the catalytic activity will decrease significantly under long-term use.
[0006] Chinese patent CN102909029A discloses a method for preparing a catalyst for producing acrylic acid, wherein: a) a metal salt containing Mo, V, W, Cu, and Sb is dispersed in deionized water with a surfactant added beforehand at 30-100°C and the reaction is maintained for 1-10 hours to form a slurry; then, the slurry is dried to obtain a dried product, which is then mixed with an amine solvent and a liquid binder after a first calcination treatment and shaped, and then calcined again to obtain the catalyst; b) the catalyst described in a) has a crystalline structure at its surface Mo-V active sites, while it has an amorphous structure in the bulk phase; c) the catalyst described in a) has a thickness of 10 μm to 3 mm at its surface Mo-V active sites; d) the metal salt described in a) is selected from ammonium molybdate, V from ammonium metavanadate, W from ammonium metatungstate, Cu from one of copper sulfate, copper acetate, and copper nitrate, and Sb from antimony acetate. The technical solution of this patent is mainly to solve the problem of excessively high hot spot temperature caused by the large accumulation of catalyst reaction heat. However, the test data disclosed in the patent text shows that the hot spot temperature of the embodiments is above 285°C, and the hot spot temperature of most embodiments is above 300°C. This indicates that the patent has not effectively solved the problem of the difficulty in quickly dissipating the accumulated catalyst reaction heat.
[0007] As can be seen above, the catalysts for the oxidation of acrolein to acrylic acid still have problems such as slow heat removal rate and high hot spot temperature. Therefore, developing a catalyst for the oxidation of acrolein to acrylic acid that can quickly remove heat of reaction, has good selectivity, high yield and good stability is of great significance for improving the quality of acrylic acid and reducing its industrial production cost. Summary of the Invention
[0008] To address the shortcomings of the existing technology, this invention provides a catalyst for acrylic acid synthesis and its preparation method, achieving the following objectives: to prepare a catalyst for acrylic acid synthesis that can rapidly remove reaction heat, has a low hot spot temperature, good selectivity, high yield, and good stability.
[0009] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A catalyst for acrylic acid synthesis and its preparation method are disclosed. The catalyst for acrylic acid synthesis has an acrolein conversion rate of 98.1-99.7%, an acrylic acid yield of 97.9-99.3%, and a hot spot temperature of 225-235℃. The preparation method of the catalyst for acrylic acid synthesis includes three steps: preparing catalyst active component powder, impregnation and loading, and drying and calcination. The following are further improvements to the above technical solution: Step 1: Preparation of catalyst active component powder Vanadium-containing compounds, molybdenum-containing compounds, and tungsten-containing compounds are added to deionized water, heated and stirred until completely dissolved to obtain a mixed salt solution. Under constant temperature stirring and reflux, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate are added to the mixed salt solution. After the reaction is complete, the solution is cooled to room temperature to obtain an active component slurry. Then, it is spray-dried and calcined to obtain catalyst active component powder. The vanadium-containing compound is one or a mixture of two of ammonium metavanadate and vanadium oxysulfate in any mass ratio; The molybdenum-containing compound is one or a mixture of two of ammonium molybdate and ammonium heptamolybdate in any mass ratio; The tungsten-containing compound is one or a mixture of two of ammonium tungstate and ammonium metatungstate in any mass ratio; The indium-containing compound is one or a mixture of two of indium sulfate and indium nitrate in any mass ratio; In the mixed salt solution, the mass ratio of vanadium-containing compound, molybdenum-containing compound, tungsten-containing compound, and deionized water is (15~39):(25~60):(5~40):(160~380). The mass ratio of the mixed salt solution, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate is (160~360):(45~100):(25~65):(6~18). The copper nitrate aqueous solution contains 20-35 wt% copper nitrate. The indium-containing compound aqueous solution contains 10-25 wt% in the indium-containing compound. The constant temperature stirring is at a temperature of 90~98℃ and a stirring speed of 400~900 rpm; The reaction is complete, and the reaction time is 3 to 7 hours; The spray drying process involves controlling the feed rate at 30-80 mL / min, the spray pressure at 0.5-0.6 MPa, the inlet temperature at 145-165℃, and the outlet temperature at 80-90℃. The roasting process involves heating at a rate of 2-3°C / min, maintaining the temperature at 450-650°C, and roasting at this constant temperature for 4-7 hours.
[0010] Step 2, Impregnation Load The active component powder of the catalyst, liquid ceramic precursor, nano silicon carbide powder, pore-forming agent and tetrahydrofuran are put into a double planetary mixer. After the air in the double planetary mixer is replaced by nitrogen, the materials in the double planetary mixer are dispersed and mixed evenly at high speed under the nitrogen-sealed and low temperature conditions to obtain an impregnation slurry. Then, silicon carbide foam is put into a vacuum vessel. After vacuuming, the impregnation slurry is drawn into the vessel using the vacuum negative pressure so that the silicon carbide foam is completely immersed in the impregnation slurry. After the impregnation is completed, the negative pressure is removed, the material is discharged and filtered, and the surface slurry of the filtered solid is blown off with air and dried at low temperature to obtain a catalyst semi-finished product. The liquid ceramic precursor is one of liquid polysilazane, liquid polycarbosilane, and liquid polyborosilazane; The number-average molecular weight of the liquid ceramic precursor is 600~2000 g / mol; The particle size of the nano-silicon carbide powder is 10~100nm; The pore-forming agent is one or a mixture of two of trihydrazine, N,N'-dicarbamoylhydrazine, and oxalic acid dihydrazine in any mass ratio; The silicon carbide foam has a porosity of 60-85% and a pore size of 20-30 ppi; The mass ratio of the catalyst active component powder, liquid ceramic precursor, nano-silicon carbide powder, pore-forming agent, and tetrahydrofuran is (85~150):(20~50):(8~20):(5~15):(55~110). The low-temperature state is characterized by a temperature control range of 25~40℃. The high-speed dispersion and mixing process involves a dual planetary mixer with a mixing speed of 100-160 rpm, a dispersion rate of 8000-12000 rpm, and a dispersion and mixing time of 10-16 hours. The static soaking time is 24-36 hours. The vacuuming process involves drawing the vacuum pressure to -0.095 to -0.1 MPa. The low-temperature drying process involves a drying temperature of 55-85℃ and a drying time of 22-38 hours.
[0011] Step 3: Drying and roasting The catalyst semi-finished product is placed in an oven and dried at 120~180℃ for 3~9 hours. Then, the catalyst semi-finished product is transferred into a muffle furnace and heated at a heating rate of 1~3℃ / min to 550~700℃. After constant temperature calcination for 6~11 hours, the product is discharged at room temperature to obtain the catalyst for acrylic acid synthesis.
[0012] Compared with the prior art, the present invention achieves the following beneficial effects: 1. In this invention, indium and tin are added to the active components of the catalyst. These two metal elements can promote the fine crystallization of the composite oxide crystal phase formed by the four active elements vanadium, molybdenum, tungsten and copper during the oxidation sintering process. This results in a composite oxide active component that not only has very high catalytic activity, but also can resist the erosion of high temperature water vapor and the thermal shock effect caused by hot spot temperature for a longer period of time. Therefore, the addition of indium and tin can play a very important synergistic effect and maintain the long-term stability of the catalyst's catalytic activity. 2. This invention uses an impregnation loading method to impregnate and coat the active catalyst component powder onto the inner and outer surfaces of silicon carbide foam. To ensure the bonding strength between the active catalyst component powder and the silicon carbide foam, a liquid ceramic precursor capable of undergoing a ceramization reaction is selected as a binder. Silicon carbide foam is chosen as the carrier mainly because of its high thermal conductivity. Through the ceramization reaction of the liquid ceramic precursor, a tight bond is promoted between the active catalyst component powder and the silicon carbide foam. In this way, the large amount of heat generated by the active catalyst component during the catalytic reaction is quickly transferred to the silicon carbide foam carrier, and then the heat of reaction is quickly removed by relying on the network skeleton structure of the silicon carbide foam. In addition, to enhance the thermal conductivity efficiency between the active catalyst component and the silicon carbide foam, this invention specifically adds nano-silicon carbide powder with high thermal conductivity during the impregnation loading process. The high thermal conductivity and large specific surface area of the nano-silicon carbide powder itself serve as a highly thermally conductive medium to promote the rapid conduction of heat from the active catalyst component powder to the silicon carbide foam carrier. 3. The liquid ceramic precursor added in this invention forms a certain covering on the active component powder of the catalyst during the ceramicization process. In order to avoid the decrease in the activity of the active component powder of the catalyst due to this covering, this invention adds a pore-forming agent and uses the thermal decomposition of the pore-forming agent to form micropores to offset the covering effect of the ceramic product, so that the active component powder of the catalyst can maintain its original high specific surface area. This can ensure the tight and high-strength bonding between the active component powder of the catalyst and the silicon carbide foam carrier, and maintain its own high catalytic activity. 4. The catalyst for acrylic acid synthesis obtained by this invention has an acrolein conversion rate of 98.1-99.7%, an acrylic acid yield of 97.9-99.3%, and a hot spot temperature of 225-235℃. Attached Figure Description
[0013] Figure 1 The image shows a 1000x magnified scanning electron microscope image of the inner surface of the catalyst for acrylic acid synthesis obtained in Example 1. Figure 2 The image shows a scanning electron microscope (SEM) image of the inner surface of the catalyst for the synthesis of acrylic acid obtained in Example 1, magnified 10,000 times. Detailed Implementation
[0014] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0015] Example 1: A method for preparing a catalyst for acrylic acid synthesis Step 1: Preparation of catalyst active component powder Vanadium-containing compounds, molybdenum-containing compounds, and tungsten-containing compounds are added to deionized water, heated and stirred until completely dissolved to obtain a mixed salt solution. Under constant temperature stirring and reflux, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate are added to the mixed salt solution. After the reaction is complete, the solution is cooled to room temperature to obtain an active component slurry. Then, it is spray-dried and calcined to obtain catalyst active component powder. The vanadium-containing compound is ammonium metavanadate; The molybdenum-containing compound is ammonium molybdate; The tungsten-containing compound is ammonium tungstate; The indium-containing compound is indium sulfate; In the mixed salt solution, the mass ratio of vanadium-containing compound, molybdenum-containing compound, tungsten-containing compound, and deionized water is 28:40:30:270; The mass ratio of the mixed salt solution, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate is 260:80:45:11. The copper nitrate aqueous solution contains 30 wt% copper nitrate. The indium-containing compound aqueous solution has a mass fraction of 15 wt%; The constant temperature stirring is at 96℃ and the stirring speed is 700 rpm; The reaction was complete, and the reaction time was 4 hours. The spray drying process involves controlling the feed rate at 60 mL / min, the spray pressure at 0.56 MPa, the inlet temperature at 155°C, and the outlet temperature at 86°C. The roasting process involves heating at a rate of 2.6°C / min, maintaining the temperature at 550°C, and roasting at that temperature for 6 hours.
[0016] Step 2, Impregnation Load The active component powder of the catalyst, liquid ceramic precursor, nano silicon carbide powder, pore-forming agent and tetrahydrofuran are put into a double planetary mixer. After the air in the double planetary mixer is replaced by nitrogen, the materials in the double planetary mixer are dispersed and mixed evenly at high speed under the nitrogen-sealed and low temperature conditions to obtain an impregnation slurry. Then, silicon carbide foam is put into a vacuum vessel. After vacuuming, the impregnation slurry is drawn into the vessel using the vacuum negative pressure so that the silicon carbide foam is completely immersed in the impregnation slurry. After the impregnation is completed, the negative pressure is removed, the material is discharged and filtered, and the surface slurry of the filtered solid is blown off with air and dried at low temperature to obtain a catalyst semi-finished product. The substance in question is liquid polysilazane; The number-average molecular weight of the liquid ceramic precursor is 1000 g / mol; The particle size of the nano-silicon carbide powder is 40 nm; The pore-forming agent is trihydrazine; The silicon carbide foam has a porosity of 75% and a pore size of 28 ppi. The mass ratio of the catalyst active component powder, liquid ceramic precursor, nano-silicon carbide powder, pore-forming agent, and tetrahydrofuran is 110:40:15:11:80. The low-temperature state is characterized by a temperature control of 30°C. The high-speed dispersion and mixing process involves a dual planetary mixer with a mixing rate of 140 rpm, a dispersion rate of 10,000 rpm, and a dispersion and mixing time of 12 hours. The static soaking time is 33 hours; The vacuum was drawn down to -0.098 MPa. The low-temperature drying process involves a drying temperature of 75°C and a drying time of 32 hours.
[0017] Step 3: Drying and roasting The catalyst semi-finished product was placed in an oven and dried at 150°C for 6 hours. Then, the catalyst semi-finished product was transferred into a muffle furnace and heated at a rate of 2°C / min until it reached 650°C. After calcining at this temperature for 8 hours, the product was discharged at room temperature to obtain the catalyst for acrylic acid synthesis.
[0018] Example 2: A method for preparing a catalyst for acrylic acid synthesis Step 1: Preparation of catalyst active component powder Vanadium-containing compounds, molybdenum-containing compounds, and tungsten-containing compounds are added to deionized water, heated and stirred until completely dissolved to obtain a mixed salt solution. Under constant temperature stirring and reflux, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate are added to the mixed salt solution. After the reaction is complete, the solution is cooled to room temperature to obtain an active component slurry. Then, it is spray-dried and calcined to obtain catalyst active component powder. The vanadium-containing compound is vanadium oxysulfate; The molybdenum-containing compound is ammonium heptamolybdate; The tungsten-containing compound is ammonium metatungstate; The indium-containing compound is indium nitrate; In the mixed salt solution, the mass ratio of vanadium-containing compound, molybdenum-containing compound, tungsten-containing compound, and deionized water is 15:25:5:160. The mass ratio of the mixed salt solution, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate is 160:45:25:6. The copper nitrate aqueous solution contains 20 wt% copper nitrate. The indium-containing compound aqueous solution has a mass fraction of 10 wt%; The constant temperature stirring is at 90℃ and the stirring speed is 400 rpm; The reaction was complete, and the reaction time was 3 hours. The spray drying process involves controlling the feed rate at 30 mL / min, the spray pressure at 0.5 MPa, the inlet temperature at 145°C, and the outlet temperature at 80°C. The calcination process involves heating at a rate of 2°C / min, maintaining the temperature at 450°C, and calcining at this temperature for 4 hours.
[0019] Step 2, Impregnation Load The active component powder of the catalyst, liquid ceramic precursor, nano silicon carbide powder, pore-forming agent and tetrahydrofuran are put into a double planetary mixer. After the air in the double planetary mixer is replaced by nitrogen, the materials in the double planetary mixer are dispersed and mixed evenly at high speed under the nitrogen-sealed and low temperature conditions to obtain an impregnation slurry. Then, silicon carbide foam is put into a vacuum vessel. After vacuuming, the impregnation slurry is drawn into the vessel using the vacuum negative pressure so that the silicon carbide foam is completely immersed in the impregnation slurry. After the impregnation is completed, the negative pressure is removed, the material is discharged and filtered, and the surface slurry of the filtered solid is blown off with air and dried at low temperature to obtain a catalyst semi-finished product. The liquid ceramic precursor is liquid polycarbosilane; The number-average molecular weight of the liquid ceramic precursor is 600 g / mol; The particle size of the nano-silicon carbide powder is 10 nm; The pore-forming agent is N,N'-dicarbamoylhydrazide; The silicon carbide foam has a porosity of 60% and a pore size of 20 ppi. The mass ratio of the catalyst active component powder, liquid ceramic precursor, nano-silicon carbide powder, pore-forming agent, and tetrahydrofuran is 85:20:8:5:55. The low-temperature state is characterized by a temperature control at 25°C. The high-speed dispersion and mixing process involves a dual planetary mixer with a mixing speed of 100 rpm, a dispersion speed of 8000 rpm, and a dispersion and mixing time of 10 hours. The static soaking time is 24 hours; The vacuum was drawn down to -0.095 MPa. The low-temperature drying process involves a drying temperature of 55°C and a drying time of 22 hours.
[0020] Step 3: Drying and roasting The catalyst semi-finished product was placed in an oven and dried at 120°C for 3 hours. Then, the catalyst semi-finished product was transferred into a muffle furnace and heated at a rate of 1°C / min until it reached 550°C. After calcining at this temperature for 6 hours, the product was discharged at room temperature to obtain the catalyst for acrylic acid synthesis.
[0021] Example 3: A method for preparing a catalyst for acrylic acid synthesis Step 1: Preparation of catalyst active component powder Vanadium-containing compounds, molybdenum-containing compounds, and tungsten-containing compounds are added to deionized water, heated and stirred until completely dissolved to obtain a mixed salt solution. Under constant temperature stirring and reflux, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate are added to the mixed salt solution. After the reaction is complete, the solution is cooled to room temperature to obtain an active component slurry. Then, it is spray-dried and calcined to obtain catalyst active component powder. The vanadium-containing compound is ammonium metavanadate; The molybdenum-containing compound is ammonium molybdate; The tungsten-containing compound is ammonium tungstate; The indium-containing compound is indium sulfate; In the mixed salt solution, the mass ratio of vanadium-containing compound, molybdenum-containing compound, tungsten-containing compound, and deionized water is 39:60:40:380; The mass ratio of the mixed salt solution, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate is 360:100:65:18. The copper nitrate aqueous solution contains 35 wt% copper nitrate. The indium-containing compound aqueous solution has a mass fraction of 25 wt%; The constant temperature stirring is at 98℃ and the stirring speed is 900 rpm; The reaction was complete, and the reaction time was 7 hours. The spray drying process involves controlling the feed rate at 80 mL / min, the spray pressure at 0.6 MPa, the inlet temperature at 165°C, and the outlet temperature at 90°C. The roasting process involves heating at a rate of 3°C / min, maintaining the temperature at 650°C, and roasting at that temperature for 7 hours.
[0022] Step 2, Impregnation Load The active component powder of the catalyst, liquid ceramic precursor, nano silicon carbide powder, pore-forming agent and tetrahydrofuran are put into a double planetary mixer. After the air in the double planetary mixer is replaced by nitrogen, the materials in the double planetary mixer are dispersed and mixed evenly at high speed under the nitrogen-sealed and low temperature conditions to obtain an impregnation slurry. Then, silicon carbide foam is put into a vacuum vessel. After vacuuming, the impregnation slurry is drawn into the vessel using the vacuum negative pressure so that the silicon carbide foam is completely immersed in the impregnation slurry. After the impregnation is completed, the negative pressure is removed, the material is discharged and filtered, and the surface slurry of the filtered solid is blown off with air and dried at low temperature to obtain a catalyst semi-finished product. The liquid ceramic precursor is liquid polyborosilazane; The number-average molecular weight of the liquid ceramic precursor is 2000 g / mol; The particle size of the nano-silicon carbide powder is 100 nm; The pore-forming agent is oxalic acid dihydrazide; The silicon carbide foam has a porosity of 85% and a pore size of 30 ppi. The mass ratio of the catalyst active component powder, liquid ceramic precursor, nano-silicon carbide powder, pore-forming agent, and tetrahydrofuran is 150:50:20:15:110. The low-temperature state is characterized by a temperature control at 40°C. The high-speed dispersion and mixing process involves a dual planetary mixer with a mixing rate of 160 rpm, a dispersion rate of 12,000 rpm, and a dispersion and mixing time of 16 hours. The static soaking time is 36 hours; The vacuum was drawn down to -0.1 MPa. The low-temperature drying process involves a drying temperature of 85°C and a drying time of 38 hours.
[0023] Step 3: Drying and roasting The catalyst semi-finished product was placed in an oven and dried at 180℃ for 9 hours. Then, the catalyst semi-finished product was transferred into a muffle furnace and heated at a heating rate of 3℃ / min to 700℃. After calcination at this temperature for 11 hours, the product was discharged at room temperature to obtain the catalyst for acrylic acid synthesis.
[0024] Comparative Example 1: Based on Example 1, in step 1, the preparation of the catalyst active component powder, in addition to the indium-containing compound aqueous solution, 45 parts of the indium-containing compound aqueous solution were replaced with 45 parts of copper nitrate aqueous solution. The specific operation is as follows: Step 1: Preparation of catalyst active component powder Replace 45 parts of indium-containing compound aqueous solution with 45 parts of copper nitrate aqueous solution, and perform the other operations as in Example 1; Steps 2 and 3 are the same as in Example 1.
[0025] Comparative Example 2: Based on Example 1, in step 1, the preparation of the catalyst active component powder, tin acetate was not added; instead, 11 parts of tin acetate were replaced with 11 parts of copper nitrate aqueous solution. The specific operation is as follows: Step 1: Preparation of catalyst active component powder Replace 11 parts of tin acetate with 11 parts of copper nitrate aqueous solution, and perform the other operations as in Example 1; Steps 2 and 3 are the same as in Example 1.
[0026] Comparative Example 3: Based on Example 1, in step 2, the impregnation load, no nano-silicon carbide powder was added. Instead, 15 parts of nano-silicon carbide powder were replaced with an equal amount of tetrahydrofuran. The specific operation is as follows: Step 1 is the same as in Example 1; Step 2, Impregnation Load Replace 15 parts of nano-silicon carbide powder with 15 parts of tetrahydrofuran, and perform the other operations as in Example 1; Step 3 is the same as in Example 1.
[0027] Comparative Example 4: Based on Example 1, in step 2, the impregnation load, no pore-forming agent was added, and 11 parts of pore-forming agent were replaced with 11 parts of tetrahydrofuran in equal amounts. The specific operation is as follows: Step 1 is the same as in Example 1; Step 2, Impregnation Load Replace 11 parts of pore-forming agent with 11 parts of tetrahydrofuran, and perform the other operations as in Example 1; Step 3 is the same as in Example 1.
[0028] Catalyst performance testing: The acrylic acid synthesis catalysts obtained in Examples 1-3 and Comparative Examples 1, 2, 3, and 4 were loaded into reaction tubes for catalytic performance testing. The reaction tubes were 30×25mm stainless steel tubes with a length of 4000mm, and a 4mm diameter stainless steel temperature measuring sleeve was inserted inside. Molten salt was used as the heat transfer medium. The reaction of acrolein oxidation to acrylic acid was simulated in a single reaction tube in an industrial setting, and the process conditions were a total space velocity of 3000 h⁻¹. -1The feed gas consisted of 8% acrolein, 10% oxygen, 35% water vapor, and the remainder nitrogen. The salt bath temperature was 220℃. The conversion rate of acrolein and the yield of acrylic acid were analyzed and calculated using gas chromatography. The average conversion rate of acrolein and the average yield of acrylic acid were statistically analyzed during 500 hours and 3000 hours of operation, and the highest hot spot temperature during the operation was recorded. The test results are shown in Table 1: Table 1
[0029] As can be seen from the test data in Table 1, the catalysts obtained in Examples 1-3, during 500 and 3000 hours of operation, showed that the highest hot spot temperature was only 15°C higher than the reaction temperature, and the conversion rate of acrolein remained above 98.1%, while the yield of acrylic acid was above 97.9%. This indicates that the acrylic acid synthesis catalyst obtained in this invention can rapidly remove the heat of reaction and also has advantages such as low hot spot temperature, good selectivity, high yield, and good stability. Comparative Examples 1 and 2, without the addition of indium-containing aqueous solutions and tin acetate respectively, showed a significant decrease in hot spot temperature. This may be due to the reduced catalytic activity, lower reaction rate, and decreased heat release. While the hot spot temperature decreased, the comparative examples... In Example 1 and Comparative Example 2, the conversion rate of acrolein and the yield of acrylic acid also decreased significantly. This may be due to the significant synergistic effect of indium and tin on improving the catalytic activity of the catalyst. In Comparative Example 3, without the addition of nano-silicon carbide powder, the hot spot temperature of Comparative Example 3 increased significantly, and the conversion rate of acrolein and the yield of acrylic acid also decreased significantly. This indicates that the addition of nano-silicon carbide powder can effectively promote the rapid removal of reaction heat within the catalyst. In Comparative Example 4, without the addition of a pore-forming agent, the hot spot temperature of Comparative Example 4 decreased significantly, and the conversion rate of acrolein and the yield of acrylic acid also decreased drastically. This may be because without the addition of a pore-forming agent, the specific surface area of the catalyst would decrease significantly, leading to a significant decrease in catalytic activity.
[0030] Appendix Figure 1 and attached Figure 2 The images shown are scanning electron microscope (SEM) images of the inner surface of the acrylic acid synthesis catalyst obtained in Example 1, magnified 1000x and 10000x, respectively. Figure 1 As can be seen, the catalyst carrier used in the synthesis of acrylic acid is open-cell foam, and the surface of the foam skeleton is very rough. This is because the surface of the foam skeleton is covered with powder of the catalyst active component. Figure 1 It can be vaguely seen that the attached catalyst active component powder is not very dense, with many tiny micropores. Figure 2The dense microporous structure visible in the image is caused by the decomposition of the pore-forming agent. This indicates that the catalyst obtained in this invention has a relatively large specific surface area, which ensures that the catalyst has a very large catalytic reaction contact site, thus exhibiting high catalytic activity. Figure 2 Furthermore, it can be observed that there are no obvious interfaces or cracks between the catalyst active component powder adhering to the surface of the silicon carbide foam and the carrier surface. This indicates that during the drying and calcination step, under the bonding and solidification effect of the liquid ceramic precursor and during the ceramicization process, the catalyst active component powder and the silicon carbide foam surface form a relatively dense and firm ceramic bonding effect. Therefore, the catalyst powder mainly composed of molybdenum, vanadium, tungsten, copper, indium, and tin oxides can be chemically bonded to the silicon carbide foam surface, thereby forming a relatively stable ceramic phase catalyst. This endows the catalyst with excellent heat resistance, airflow erosion resistance, and very good high thermal conductivity, thus possessing long-term stability and maintaining the long-term non-decay of catalytic activity and efficient removal of reaction heat during the long-term use cycle of the catalyst.
[0031] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst for acrylic acid synthesis, characterized in that: The preparation method of the catalyst for acrylic acid synthesis includes three steps: preparing catalyst active component powder, impregnation and loading, and drying and calcination. The preparation of the catalyst active component powder involves adding vanadium-containing compounds, molybdenum-containing compounds, and tungsten-containing compounds to deionized water, heating and stirring until completely dissolved to obtain a mixed salt solution. Under constant temperature stirring and reflux conditions, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate are added to the mixed salt solution. After the reaction is complete, the solution is cooled to room temperature to obtain an active component slurry. Then, the slurry is spray-dried and calcined to obtain the catalyst active component powder. The indium-containing compound is one or a mixture of two of indium sulfate and indium nitrate in any mass ratio; The impregnation loading process involves placing the catalyst active component powder, liquid ceramic precursor, nano-silicon carbide powder, pore-forming agent, and tetrahydrofuran into a double planetary mixer. After replacing the air inside the double planetary mixer with nitrogen, the materials are dispersed and mixed evenly at high speed under nitrogen sealing and low temperature conditions to obtain an impregnation slurry. Then, silicon carbide foam is placed into a vacuum vessel, and after evacuation, the impregnation slurry is drawn into the vessel using vacuum negative pressure to completely immerse the silicon carbide foam in the impregnation slurry. The impregnation is allowed to stand for impregnation. After impregnation is completed, the negative pressure is removed, the material is discharged and filtered, and the filtered solid is cleaned of the surface slurry with air and then dried at low temperature to obtain a catalyst semi-finished product. The liquid ceramic precursor is one of liquid polysilazane, liquid polycarbosilane, and liquid polyborosilazane; The number-average molecular weight of the liquid ceramic precursor is 600~2000 g / mol; The particle size of the nano-silicon carbide powder is 10~100nm; The pore-forming agent is one or a mixture of two of trihydrazine, N,N'-dicarbamoylhydrazine, and oxalic acid dihydrazine in any mass ratio; The silicon carbide foam has a porosity of 60-85% and a pore size of 20-30 ppi.
2. The method for preparing the catalyst for acrylic acid synthesis according to claim 1, characterized in that: The vanadium-containing compound is one or a mixture of two of ammonium metavanadate and vanadium oxysulfate in any mass ratio; The molybdenum-containing compound is one or a mixture of two of ammonium molybdate and ammonium heptamolybdate in any mass ratio; The tungsten-containing compound is one or a mixture of two of ammonium tungstate and ammonium metatungstate in any mass ratio.
3. The method for preparing the catalyst for acrylic acid synthesis according to claim 1, characterized in that: In the mixed salt solution, the mass ratio of vanadium-containing compound, molybdenum-containing compound, tungsten-containing compound, and deionized water is (15~39):(25~60):(5~40):(160~380). The mass ratio of the mixed salt solution, copper nitrate aqueous solution, indium-containing compound aqueous solution, and tin acetate is (160~360):(45~100):(25~65):(6~18). The copper nitrate aqueous solution contains 20-35 wt% copper nitrate. The indium-containing compound aqueous solution has a mass fraction of 10-25 wt%.
4. The method for preparing the catalyst for acrylic acid synthesis according to claim 1, characterized in that: The mass ratio of the catalyst active component powder, liquid ceramic precursor, nano silicon carbide powder, pore-forming agent, and tetrahydrofuran is (85~150):(20~50):(8~20):(5~15):(55~110).
5. The method for preparing the catalyst for acrylic acid synthesis according to claim 1, characterized in that: The drying and calcination process involves placing the catalyst semi-finished product in an oven and drying it at 120~180℃ for 3~9 hours. Then, the catalyst semi-finished product is transferred into a muffle furnace and heated at a rate of 1~3℃ / min until it reaches 550~700℃. After calcining at this constant temperature for 6~11 hours, the product is discharged at room temperature to obtain the catalyst for acrylic acid synthesis.
6. A catalyst for the synthesis of acrylic acid prepared by the preparation method according to any one of claims 1-5.
Citation Information
Patent Citations
Preparation method of catalyst for acrylic acid by oxidizing acraldehyde
CN102039143A
Preparing method of catalyst for producing crylic acid
CN102909029A
Supported catalyst for preparation of acrylic acid
CN110586119A
Synthetic method of acrylic acid
CN110590536A
Catalyst for acrylic acid synthesis, and method for synthesizing acrylic acid from acrolein
CN111068652A
Cited By
Supported acrolein selective oxidation catalyst and preparation method thereof
CN121467022A
A supported propylene aldehyde selective oxidation catalyst and a method for preparing the same
CN121467022B